Artificial intelligence in healthcare: transforming the practice of medicine - Bajwa, Junaid; Nori, Aditya; Williams, Bryan; Munir, Usman (Future Healthcare Journal, 2021)
Artificial intelligence (AI) is a powerful and disruptive area of computer science, with the potential to fundamentally transform the practice of medicine and the delivery of healthcare. In this review article, we outline recent breakthroughs in the application of AI in healthcare, describe a roadmap to building effective, reliable and safe AI systems, and discuss the possible future direction of AI augmented healthcare systems.